The end of "white gold" in the mountains? - Sophie Madelrieux; Maud Hirczak; Agnès Bergeret; Françoise Alavoine-Mornas (Revue de Géographie Alpine)
With the end of milk quotas, mountain producers find themselves in direct competition with all dairy producers. This reinforces the need for mountain areas to stand out from lowland areas to avoid frontal competition over mass productions. But some mountain areas, engaged in this mass production are worried, this is the case of Sud-Isère. In order to reflect on the future of dairy production in this mountain area, various stakeholders came together to question possible futures in the framework of an action research project. Interactions between the geography of production and the geography of processing, particularly the forms of interactions between dairy value chain and territories, and their evolution over time were questioned. Based on: i) an analytical framework combining works on territorial embeddedness and processes of change; ii) a system combining historical research, statistical data, field surveys and a number of meetings in the area, notably around a knowledge sharing during a workshop “historical frieze”, we analyze the successive forms of embeddedness and distancing between dairy sectors and territories in the Sud-Isère. We discuss what they might be in the future, particularly by confronting the dynamics of other dairy basins.